Discrete-time modelling and behaviour analysis of an N-cell DC/DC buck converter. (2016) - KoubaÁ¢, Karama; Feki, Moez
Multi-cell converters were developed as a result of a growing need for higher power converters. They permit to reduce the voltage across the switches and the output voltage harmonics. In this paper, we propose a discrete model for a multi-cell DC/DC buck converter controlled by a proportional controller using the pulse width modulator technique. A detailed stability analysis is given with illustrative simulation results, which show that increasing the value of the current gain of the proportional controller leads to a chaotic behaviour.